Understanding the mechanism of low temperature deactivation of Cu/SAPO-34 exposed to various amounts of water vapor in the NH3-SCR reaction. Issue 14 (6th June 2019) - Woo, Jungwon; Bernin, Diana; Ahari, Homayoun; Shost, Mark; Zammit, Michael; Olsson, Louise
Abstract : Water-exposure at 70 °C deteriorates Cu/SAPO-34, the extent of which depends on water exposure time, reaction temperature, and choice of SDAs. Abstract : The low temperature hydrothermal stability of Cu/SAPO-34 catalysts for the NH3 -SCR reaction, prepared by three different structure directing agents (SDAs), i.e., morpholine (MO), triethylamine (TEA), and tetraethylammonium hydroxide (TEAOH), was investigated by exposing them to various amounts of water vapor. XRD and BET studies indicate that there was no sign of Cu/SAPO-34 catalyst's chabazite (CHA) structural collapse due to water vapor exposure up to 55 h regardless of SDA choice. However, a multinuclear solid-state magic angle spinning (SS-MAS) NMR study of Cu/SAPO-34(MO, TEA, TEAOH) suggests that the water vapor exposure had significantly altered the coordination environment of Al, P, and Si, the extent of which depends on the choice of SDA along with water vapor exposure time. NO-DRIFTS and H2 -TPR studies suggest different mobility for Cu ions between the 6MR and 8MR of the CHA structure in Cu/SAPO-34(MO, TEA, TEAOH) as the result of water vapor exposure and during the NH3 -SCR reaction. The mechanisms for low temperature deactivation of Cu/SAPO-34 were proposed as follows: 1) irreversible Si condensation in the support and 2) Cu migration to less accessible sites and/or formation of CuO x clusters depending on Cu mobility.